2022
DOI: 10.3390/metabo12020161
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Serum Metabolomic Profile for the Radiomitigative Effect of the Thrombopoietin Receptor Agonist Romiplostim in Lethally Whole-Body-Irradiated Mice

Abstract: The thrombopoietin receptor agonist romiplostim (RP) was recently approved by the US Food and Drug Administration for improving survival in patients acutely exposed to myelosuppressive doses of radiation. Our previous studies with mice have shown that RP administration after lethal irradiation not only completely rescues irradiated mice but also shows mitigative effects on their hematopoiesis and multiple organ injury, including that of the lung, bone marrow, small intestine, and liver. However, the mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 62 publications
0
4
1
Order By: Relevance
“…In the present study, we have observed upregulation of amino acid at 24 h post radiation exposure which is in concurrence with the previous studies that had also shown changes in amino acids like valine, proline, glutamate, histidine, alanine, arginine, alanine, and asparagine, tyrosine in NHP serum after IR 39 . Recently, changes in histidine metabolism have also been observed by Sato et al, though the changes observed were in contrast to our findings 41 . Some of these changes complement pathways based on transcriptomic data for their validation.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, we have observed upregulation of amino acid at 24 h post radiation exposure which is in concurrence with the previous studies that had also shown changes in amino acids like valine, proline, glutamate, histidine, alanine, arginine, alanine, and asparagine, tyrosine in NHP serum after IR 39 . Recently, changes in histidine metabolism have also been observed by Sato et al, though the changes observed were in contrast to our findings 41 . Some of these changes complement pathways based on transcriptomic data for their validation.…”
Section: Discussioncontrasting
confidence: 99%
“…Our previous studies showed that the thrombopoietin receptor agonist RP, a drug used for the treatment of idiopathic thrombocytopenic purpura, completely rescued mice exposed to lethal TBI [13], and the radio-mitigative effects of RP were also reported by other groups [11,12]. However, the mechanism of action of RP cannot be explained by signal transduction via the thrombopoietin receptor alone, and significant efforts were made to understand the mechanisms for achieving this life-saving effect [15][16][17][18]. In the present study, to further elucidate the radio-mitigative effect mechanism of the domestically approved drug RP, we focused on EVs that were collected from the sera of mice that overcame severe ARS and avoided mortality with the administration of RP, and performed a basic study on the radiomitigative and life-saving effects of their EVs on mice acutely exposed to myelosuppressive doses of ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The thrombopoietin receptor agonist RP (Romiplate ® , Kyowa Kirin, Tokyo, Japan), as an ARS mitigator, was intraperitoneally administered once daily for 3 consecutive days to irradiated mice, starting immediately after TBI (within 2 h, 24 h, and 48 h post-TBI). The applied dose of RP was 50 µg/kg of body weight/day prepared with Normal Saline Solution (NSS; Otsuka Pharmaceutical, Tokyo, Japan) as the vehicle [13][14][15][16][17][18]. In addition to mice that received both TBI and RP (TBI + RP group), mice treated with TBI and NSS (TBI + NSS group), mice treated with RP only (0 Gy + RP group), and those treated with NSS only (0 Gy + NSS group) were prepared in this study.…”
Section: Administration Of Ars Protective/mitigative Agentsmentioning
confidence: 99%
See 2 more Smart Citations